Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Nasabah PT Pegadaian Persero Cabang Gubug Kabupaten Grobogan - Hermawan Budiyanto (CiDEA Journal, 2023)
The study aims to analyze the impact of product quality and service quality on customer satisfaction in Pegadaian Pesero Branch Gubug district of Grobogan. The design of this research uses a quantitative approach. Samples are taken by random sampling. The method of analysis used is to test the product moment hypothesis. The results of the research indicate that this Product Quality has a positive impact on Customer Satisfaction, as well as on the Quality of Service has a negative impact on customer satisfaction. Simultaneously, both Product Quality and Service Quality together have a positive effect on the Customer satisfaction in Pegadaian Pesero Branch Gubug district of Grobogan.